2021
DOI: 10.1007/s10865-021-00254-6
|View full text |Cite
|
Sign up to set email alerts
|

Day-to-day associations between sleep and physical activity: a set of person-specific analyses in adults with overweight and obesity

Abstract: The objective of the present study was to estimate whether physical activity on one day was associated with both sleep quality and quantity the following night and to examine to what extent sleep on one night was associated with physical activity the next day. We collected data from 33 young adults who were overweight or obese and consistently wore a Fitbit Charge 3. A total of 7094 days and nights were analyzed. Person-specific models were conducted to test the bi-directional associations for each participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
8
1
Order By: Relevance
“…Sleep duration was significantly decreased following HIIE. This was supported by a day-to-day study that indicated there was a negative association between steps and sleep duration [ 63 ]. However, some studies suggested that exercises were an effective strategy to improve sleep duration.…”
Section: Discussionmentioning
confidence: 69%
“…Sleep duration was significantly decreased following HIIE. This was supported by a day-to-day study that indicated there was a negative association between steps and sleep duration [ 63 ]. However, some studies suggested that exercises were an effective strategy to improve sleep duration.…”
Section: Discussionmentioning
confidence: 69%
“…increasing or introducing X causes Y to decrease). Rather, we created our a priori hypotheses based on both the findings of 71 and our own experiences and reflections.…”
Section: Methodsmentioning
confidence: 99%
“…time frame of available data). These are the time series linear models fit by, 71 combinations of which might together comprise a vector autoregression. "Granger" refers to so-called "Granger causality," which by causal inference definition is in fact only an association/correlation/prediction of one time series with another time series-not a causal effect of one time series on another, as we are attempting to estimate in this study.…”
Section: Methodsmentioning
confidence: 99%
“…For example, one can examine varying the exposure to factors that impact the physiologic sleep drive to infer the APTE of that factor on sleep. Chevance et al (2021) [46] examined such associations, but stopped short of attempting to draw causal inferences. A reasonable treatment phase or period could be one day, given that periods of sleep, by their very nature, tend to "wash out" the effect of increased sleep pressure resulting from increased levels of waking activity.…”
Section: Why Study Sleep?mentioning
confidence: 99%
“…However, simply getting more sleep leaves one less time to take steps the following day. Hence, raw step count is often associated with sleep duration [46], regardless of how it might affect sleep duration (i.e., our APTE of interest).…”
Section: Data-generating Proceduresmentioning
confidence: 99%